State Immunity and Inter-State Negotiations on Korean Comfort Women - Liakopoulos, Dimitris (Indonesian Journal of International Law, 2022)
This study aims to analyze the situation of comfort women and the acquired jurisprudence, as well as a comparison regarding slavery and the protection of human rights at the international level. It also examines the protection of human rights, international responsibility, crimes committed with impunity, interstate agreements, state immunity, victim reparation, and international jurisprudence. A comparative method was used to analyze tribunal sentences at the International Court of Justice (ICJ) or the national level of Italian constitutional law. However, international responsibility is important because it helps to protect slavery and human rights. The argument of comfort women includes the right access to justice at the international and national levels. Furthermore, it is related to victim participation and the protection that is necessary to be involved in any jurisprudence.